Improved ship position stability on offshore-based dynamic position maintenance with the PID method - Dutopo, Hermono; Marwanto, Arief; Alifah, Suryani; Hidayah, Malikhatul (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Anchor Handling Tug and Supply (AHTS) vessel is a type of vessel designed to support oil and gas drilling facility activities and work, in addition to serving offshore oil and gas exploration work. The special feature of this ship is that the hull is not too large, equipped with a large auxiliary engine with propeller driving (double) at the rear and equipped with maneuvering aids to maintain position, namely Bow Thruster, Stern Thruster and Dynamic Position System for AHTS ships so that they can work maneuvering at sea to be fast and accurate in determining the ship's position. One solution to overcome this problem in this research is to create a control simulation so that the ship remains stable in a state of floating above the offshore waters. The control method used is a PID-based dynamic method. The sensors used are accelerometers and gyroscopes that can read the movement and angle changes in the blood vessels. From the results of testing and analysis of parameters Kp: 60, Ki: 2, and Kd: 30 for ship control gave good results, namely the ship will return to its original position when it floats.